A Comparative Analysis of Phytochemical Content and Extractive Efficiency in Curcuma Species: Profiling Total Phenolics, Flavonoids, and Alkaloids - Mali Seeta Vitthal, Vishal Gupta (Journal of Neonatal Surgery, 2025)
The present investigation explores the comparative phytochemical profiles, extractive efficiencies, and bioactive compound content of three Curcuma species, Curcuma zedoaria, Curcuma caesia, and Curcuma amada using solvents of varying polarities: ethyl acetate, ethanol, and water. Extraction yields varied among species, with aqueous extracts showing the highest yields in C. caesia (1.94%) and C. amada (2.28%), while ethanol proved most effective for C. zedoaria (1.36%), indicating a solvent-dependent distribution of phytoconstituents. Phytochemical screening revealed distinct patterns of bioactive compounds across species and extracts. Ethanolic extracts of C. caesia and C. amada showed a rich diversity of secondary metabolites, including alkaloids, flavonoids, phenols, and diterpenes. Quantitative analysis supported these findings, with C. caesia exhibiting the highest phenolic (2.56 mg/100 mg GAE) and flavonoid (2.97 mg/100 mg QE) content, while C. amada had the highest alkaloid content (1.43 mg/100 mg AE). C. zedoaria, although less chemically diverse, demonstrated notable extractive efficiency with ethanol and may possess selective antimicrobial potential. Overall, C. caesia emerged as the most phytochemically potent species, while C. amada showed promising alkaloid-associated bioactivity. These findings provide a scientific foundation for the selection of appropriate Curcuma species and extraction methods for therapeutic, nutraceutical, or pharmacological applications.